Seizing power the grab for global oil wealth - Slater, Robert; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2010)
"Since the 1973-1974 Arab oil embargo, oil-rich outlaw nations have become petroaggessors and used a valuable natural resource as a weapon in global politics. Seizing Power takes a look at Putin, Chavez, Ahmadinejad, and other key players whose hunger for power and money has framed some stark choices. Where should the ethical person stand in the fight to maintain affordable energy, keep the planet green, implement ethical business policies, and guard basic human rights? New York Times best-selling author Robert Slater lays out the alternatives. In a climate of dwindling oil, only by being realistic about energy options can readers make informed choices"--Provided by publisher.
Machine generated contents note: Acknowledgments. -- Introduction: The Parable of Sao Tome;. -- 1 Edging Toward Violence and Chaos. -- 2 Two African Oil Nations: A Study in Contrasts. -- 3 China Invades Africa. -- 4 Power in the Desert: The Gulf and the Middle East. -- 5 Testing the Oil System: The War, the Embargo, and Spare Capacity. -- 6 The History of Oil and the American Dream. -- 7 Ethics and Oil. -- 8 Hedging: Insurance or Speculation? -- 9 How Much Oil Is Left ... and How Willing Is the United States to Drill for It? -- 10 Oil for the Lamps of China ... and India. -- 11 Power Shift. -- 12 Russia: Putin's War Against the Oligarchs. -- 13 Iran: Arrogance as an Oil Strategy. -- 14 Venezuela: The World According to Chavez. -- 15 Brazil and Petrobras: A National Oil Company in a Better World. -- 16 After the Power Shift: Where Will It All Lead? -- List of Illustrations. -- Index.
Includes index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Petroleum reserves; Petroleum industry and trade; Electronic books